To Sense or not to Sense: An Exploratory Study of Privacy, Trust and other related concerns in Personal Sensing Context-aware Applications - Bhargava, Preeti; Gramsky, Nick; Agrawala, Ashok (EAI Endorsed Transactions on Context-aware Systems and Applications, 2016)
Due to increasing proliferation of smart devices, many users store a significant proportion of personal data on them. Thus, personal sensing applications that sense a user’s context via his smart device have significant privacy implications. In this paper, we conduct an exploratory study of privacy, trust, risks and other concerns of users with smart phone based context-aware personal sensing systems and applications. Our study results show that users are concerned that their sensed data can be misused, used for personal identification and tracking or for commercial purposes. However, they are willing to trade privacy for additional benefits if their sensed information is used for effective and beneficial causes. Furthermore, they are willing to trust reputed technology companies, with their data, if the benefits are significant. Based on these results, we propose a few design guidelines for designers of personal sensing apps and outline some interesting directions for future research.